Genetic polymorphisms of PPAR gamma, arsenic methylation capacity and breast cancer risk in Mexican women - Cristina P Pineda-Belmontes; Raúl U Hernández-Ramírez; César Hernández-Alcaraz; Mariano E Cebrián; Lizbeth López-Carrillo (Instituto Nacional de Salud Pública, 2016)
Objective. To evaluate whether the presence of polymorphisms of peroxisome proliferator-activated receptor gamma PPARγ (Pro12Ala) and PPARGC1B (Ala203Pro) modifies the association between the inorganic arsenic (iAs) methylation capacity and breast cancer (BC). Materials and methods. Mexican women were interviewed, and blood and urine samples were collected from them (cases/controls= 197/220). The concentration of urinary arsenic species and the polymorphisms of interest were determined by high-performance liquid chromatography with inductively coupled plasma mass spectrometry (HPLC-ICP-MS) and polymerase chain reaction (PCR), respectively. Results. In women with a high %MMA (urinary monomethyl arsenic) and high primary methylation ratio (PM = MMA/iAs), the risk of BC was increased (odds ratio [OR]%MMA T3vs.T1= 3.60: 95% confidence interval [CI] 2.02-6.41, ORPMI T3vs.T1= 3.47: 95%CI 1.95-6.17), which was maintained after adjusting for polymorphisms. No significant interactions were observed between the polymorphisms and the arsenic variables on the risk of BC. Conclusion. Pro12Ala and Ala203Pro polymorphisms did not modify the association between the iAs methylation capacity and BC. DOI: http://dx.doi.org/10.21149/spm.v58i2.7791